A study of different statistical analysis methods to monitor the stock prices - Lee, Mary Gion Ein (2019)
The stock exchange is a regulated financial market and it reflect a country’s growth and performance. The stock market is essential as it can directly affect the economy of a country. In this project, seven stocks in Malaysia are picked and studied by applying Shewhart